Linewidth of a quantum cascade laser assessed from its frequency noise spectrum and impact of the current driver - Tombez, Lionel; Schilt, Stephane; Di Francesco, Joab; Di Domenico, Gianni; Hofstetter, Daniel; Thomann, Pierre (My University, 2012)
We report on the measurement of the frequency noise properties of a 4.6-μm distributed-feedback quantum-cascade laser (QCL) operating in continuous wave near room temperature using a spectroscopic set-up. The flank of the R(14) ro-vibrational absorption line of carbon monoxide at 2196.6 cm^−1 is used to convert the frequency fluctuations of the laser into intensity fluctuations that are spectrally analyzed. We evaluate the influence of the laser driver on the observed QCL frequency noise and show how only a low-noise driver with a current noise density below ≈1 nA/√Hz allows observing the frequency noise of the laser itself, without any degradation induced by the current source. We also show how the laser FWHM linewidth, extracted from the frequency noise spectrum using a simple formula, can be drastically broadened at a rate of ≈1.6 MHz/(nA/√Hz) for higher current noise densities of the driver. The current noise of commercial QCL drivers can reach several nA/√Hz , leading to a broadening of the linewidth of our QCL of up to several megahertz. To remedy this limitation, we present a low-noise QCL driver with only 350 pA/√Hz current noise, which is suitable to observe the ≈550 kHz linewidth of our QCL.